2021
DOI: 10.3174/ajnr.a6998
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics of Pediatric Low-Grade Gliomas: Toward a Pretherapeutic Differentiation of BRAF-Mutated and BRAF-Fused Tumors

Abstract: BACKGROUND AND PURPOSE: B-Raf proto-oncogene, serine/threonine kinase (BRAF) status has important implications for prognosis and therapy of pediatric low-grade gliomas. Currently, BRAF status classification relies on biopsy. Our aim was to train and validate a radiomics approach to predict BRAF fusion and BRAF V600E mutation. MATERIALS AND METHODS: In this bi-institutional retrospective study, FLAIR MR imaging datasets of 115 pediatric patients with low-grade gliomas from 2 children's hospitals acquired betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 44 publications
0
37
0
1
Order By: Relevance
“…RF has been a popular data mining and statistical tool in radiomics research due to its transparency and success in classi cation and regression tasks (20,(30)(31)(32)(33). It generates a large number of decision trees using random subsamples of the training data while also randomly varying the features used in the trees (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RF has been a popular data mining and statistical tool in radiomics research due to its transparency and success in classi cation and regression tasks (20,(30)(31)(32)(33). It generates a large number of decision trees using random subsamples of the training data while also randomly varying the features used in the trees (34).…”
Section: Discussionmentioning
confidence: 99%
“…The datasets of 94 patients from The Hospital for Sick Children, Toronto, and 21 patients from The Lucile Packard Children's Hospital, Stanford, used in this study have been previously published (20). The previous study applied an RF model without variations in sample size to differentiate BRAF fused from BRAF V600E mutated pLGG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF status was predicted with an AUC of 0.75 (SD, 0.12) and (95% confidence interval 0.62–0.89) for the internal validation cohort through a fourfold cross-validation scheme, and AUC for the external validation was 0.85. Age and tumor location were significant predictors of BRAF status, while sex was not a significant predictor [ 119 ].…”
Section: Radiomics Of Pediatric Brain Tumorsmentioning
confidence: 99%
“…A recent study showed the ability of radiomics-based prediction of BRAF status in pediatric low-grade gliomas before a biopsy, which could have significant implications in clinical practice. 91 Immunology. Use of immunotherapeutic strategies, including adoptive cell therapy, vaccine therapy, and checkpoint inhibitors, in pediatric brain tumors has been rapidly evolving.…”
Section: Evolving Era Of Radiomics In Pediatric Neuro-oncologymentioning
confidence: 99%